Chemical modification-mediated optimisation of bronchodilatory activity of mepenzolate, a muscarinic receptor antagonist with anti-inflammatory activity. Issue 15 (1st August 2019) - Yamashita, Yasunobu; Tanaka, Ken-ichiro; Yamakawa, Naoki; Asano, Teita; Kanda, Yuki; Takafuji, Ayaka; Kawahara, Masahiro; Takenaga, Mitsuko; Fukunishi, Yoshifumi; Mizushima, Tohru
Graphical abstract: Abstract: The treatment for patients with chronic obstructive pulmonary disease (COPD) usually involves a combination of anti-inflammatory and bronchodilatory drugs. We recently found that mepenzolate bromide (1 ) and its derivative, 3-(2-hydroxy-2, 2-diphenylacetoxy)-1-(3-phenoxypropyl)-1-azoniabicyclo[2.2.2]octane bromide(5), have both anti-inflammatory and bronchodilatory activities. We chemically modified5 with a view to obtain derivatives with both anti-inflammatory and longer-lasting bronchodilatory activities. Among the synthesized compounds, ( R )-(–)-12 (( R )-3-(2-hydroxy-2, 2-diphenylacetoxy)-1-(3-phenylpropyl)-1-azoniabicyclo[2.2.2]octane bromide) showed the highest affinity in vitro for the human muscarinic M3 receptor (hM3 R). Compared to1 and5, ( R )-(–)-12 exhibited longer-lasting bronchodilatory activity and equivalent anti-inflammatory effect in mice. The long-term intratracheal administration of ( R )-(–)-12 suppressed porcine pancreatic elastase-induced pulmonary emphysema in mice, whereas the same procedure with a long-acting muscarinic antagonist used clinically (tiotropium bromide) did not. These results suggest that ( R )-(–)-12 might be therapeutically beneficial for use with COPD patients given the improved effects seen against both inflammatory pulmonary emphysema and airflow limitation in this animal model.